HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR GULA DARAH PUASA PADA PEGAWAI SEKRETARIAT DAERAH PROVINSI RIAU - Muhammad Arif; Yanti Ernalia; Dani Rosdiana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The Incidence of type 2 Diabetes Mellitus in Indonesia tends to increase inlast 10 years. This has become a more serious problem especially since diabetesis often undiagnosed due to severe complications occur on long period enough(undiagnosed DM). Because of that screening for blood glucose levels isnecessary to detect diabetes mellitus. On the other hand several studies foundthat Body Mass Index (BMI) also has correlation too with blood glucose levels.Civil servants is a group of people at high risk of developing obesity, whereobesity itself is one of risk factor for increased level of blood glucose. Themeasurements of fasting blood glucose with enzymatic method and body massindex in 43 civil servans of Sekretariat Daerah Provinsi Riau which whom neverdiagnosed as diabetes mellitus has been tested. And the correlation between theBMI and fasting blood glucose has been computed. Spearman test result the Pscores is 0.276 (P>0.05) and therefore concludes that there is no correlationbetween Body Mass Index and Fasting Blood Glucose in this researchKeywords : Diabetes Mellitus, Body Mass Index, Fasting Blood Glucose, Civilservants